Assessment of caesarean section and inguinal hernia repair as proxy indicators of total number of surgeries. (27th April 2015) - Bjerring, Anders Wold; Lier, Marius E; Roed, Siri M; Vestby, Pia F; Endreseth, Birger H; Salvesen, Øyvind; von Schreeb, Johan; Wibe, Arne; Kamara, T B; Bolkan, Haakon A
Abstract: Background: The traditional instruments used to assess surgical capacity in low-income countries require substantial amounts of time and resources, and have thus not been systematically used in this context. Proxy indicators have been suggested as a simpler method to estimate surgical volume. The aim of this study was to assess caesarean section and inguinal hernia repair as proxy indicators of the total number of surgeries performed per capita in a given region in Sierra Leone in sub-Saharan Africa. Methods: Avaliable handwritten surgical data were compiled from 58 (96·7%) health institutions that performed WHO defined major surgery in Sierra Leone in 2012 (from Jan 1, to Dec 31). 24 152 surgical procedures were included in the study. Validity of proxy indicators was tested by logistic regression analyses with the rate of caesarean sections compared with total operations (% CS), hernia repairs (% HR), or both (% CS plus HR) as dependent variables and the operations per 100 000 capita as the covariate. Findings: The number of operations per 100 000 capita for the 13 districts of Sierra Leone varied from 909 in the urban Western District to 32 in the rural district of Moyamba. There was a significant negative correlation between each of the proxy indicators and the number of operations per 100 000 capita. For changes in the operations per 100 000 capita of 100, we obtained an estimated odds ratio for the % CS proxy indicator of 0·675 (95% CI 0·520–0·876; p<0·01), % HR being 0·822 (0·688–0·983; p<0·05), and for % CS plus HR being 0·838 (0·731–0·962; p<0·05). Interpretation: The unmet need for surgical services in Sierra Leone can be estimated by either of the three proxy indicators. However, it seems that % CS is more sensitive to small changes in operations per 100 000 capita compared with the % HR. There is no obvious added benefit of use of the combined proxy indicator. Although this study shows that proxy indicators are a promising method to evaluate surgical activity, this is a cross-sectional study and can thus only show correlation. Longitudinal studies would strengthen these findings. Funding: Faculty of Medicine, Norwegian University of Science and Technology, Trondheim, Norway, and CapaCare.